MINAT PEMILIHAN PERGURUAN TINGGI DAN PERAN KELOMPOK REFERENSI SERTA KOMUNIKASI PEMASARAN TERINTEGRASI - Yuli Harwani; Budi Suharjo; Rita Nurmalina; Gendut Suprayitno (Universitas Mercu Buana, 2018)
Abstract. This study aims to examine the role of reference groups and integrated marketing communications with the intention of college selection through the mediation of attitudes and subjective norms of consumers. The analysis is done from the perspective of high school students in Indonesia as a developing country. The survey was conducted on 432 students with 91.90 percent of respondent's data that can be analyzed. Data analysis and model testing are proposed using Structural Equation Modeling - Lisrel. The result of the analysis shows that there is an influence of the reference group, integrated marketing communications, attitude and subjective norm toward the intention of college selection. These results provide an overview to the college managerial to develop an integrated marketing communication strategy aimed not only at the consumers of high school students, but also those who play a role in influencing the electoral process such as schools, friends and families, especially parents. Empirically, the results of this study indicate that college consumers in Indonesia in this study are high school students assess that integrated reference groups and marketing communications have an important role in influencing their electoral intention. Subsequently found, the reference group and integrated marketing communications affect the intention of college selection with the mediation of attitude and subjective norms.